ANALISIS KEPATUHAN PENGISIAN RESUME MEDIS ELEKTRONIK RAWAT INAP KSM KESEHATAN ANAK GUNA MENUNJANG KUALITAS REKAM MEDIS DI RSUP Dr. HASAN SADIKIN BANDUNG - Wowo Trianto; Neni Rohaeni (UPPM Politeknik TEDC Bandung, 2021)
Based on preliminary studies conducted by the author at Dr. Hasan Sadikin General Hospital Bandung with an average of 760 of KSM Child Health patients per month while the number of completions filling electronic medical resumes is only 87%. The author is interested in examining the completeness of filling out an electronic medical resume to support the quality of medical record files at RSUP Dr. Hasan Sadikin Bandung.The research method used is a quantitative research method. Population is the total number of patients going home KSM Child Health in December 2019 and the sampling used by the author with the Slovin formula method obtained a sample of 90 files of Medical Records. Data collection techniques are with Documentation, Interview, and Literature Study. The results showed that as many as 22.62% of electronic medical resume files were not completely filled. The procedure for filling out an electronic medical resume has not been carried out well due to the doctor's busyness, the large number of KSM Child Health patients, there is still a medical resume written manually, There are still inadequate infrastructure.The author recommends conducting socialization to the patients in charge of patients to always complete electronic medical resume filling, provide adequate infrastructure, and provide rewards and punishments for doctors who do not complete electronic medical resumes completely.